Long-term post-release evaluation shows Hypogeococcus sp. is an effective biological control agent for queen of the night cactus in South Africa - Muskett, Phillippa; Sutton, G. F.; Paterson, I. D. (Biocontrol science and technology, 2024)
We conducted long-term monitoring of Hypogeococcus sp. (Pseudococcidae) as a biocontrol agent for queen of the night cactus (Cereus jamacaru De Candolle). The biocontrol agent was released at three sites representing the regions where the plant is problematic in South Africa, and both agent and plant populations were monitored over time. The proportion of plants producing fruits or flowers decreased by 36% each year, with all plants no longer flowering between two and seven years after release. Plant density reduced by 42% each year after release. Hypogeococcus sp. is an effective agent against C. jamacaru in South Africa.